The relationship between gonadotropin and sexual behaviour of male Trichogaster trichopterus (Pallas) - Mananos, E; Zohar, Y; Degani, G (Indian Journal of Fisheries, 2011)
The levels of gonadotropin (GtH-II) in the plasma and pituitary, and of thesteroids testosterone (T) and progesterone (P) in the plasma and testes, weremeasured in male blue gourami (Trichogaster trichopterus) during sexualbehaviour (before and during nest building and during courtship). In thepituitary of nest-building and courting males, the levels of GtH-II (1854 ±112and 1520±112 ng/mg protein, respectively) were higher than in males thatwere not building nests (10781112 ng/mg protein); while in the plasma, GtHIIlevels were 7 ± 1.5, 6 + 1 . 1 and 4.6 ±1.1 ng/ml, respectively. The samepattern was found in the levels of plasma T:3.6 ± 1.0, 2.4 ± 0.8 and 1.5±0.8ng/ml, respectively), though no significant difference was found in the testes.Similarly, the levels of P in the testes were 4 ± 1.0, 3.8 + 0.9 and 2 ± 0.9 ng/ml, respectively. The relationship between GtH-II and male sexual behaviouris discussed.